2021
DOI: 10.1093/femsle/fnab149
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome status of urban and rural Filipino adults in relation to diet and metabolic disorders

Abstract: Here, we aim to understand the condition of the gut microbiome of Filipino adults in relation to their diet and metabolic status. Compared to rural Albay (n = 67), the gut microbiome of subjects living in urban Manila (n = 25) was more colonized by the order Clostridiales, which was negatively correlated with host carbohydrate consumption. Principal component analysis using the genus composition of the 92 total subjects indicated four microbiome types: one type driven by Prevotella, which was associated with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…In this study, one-third of all participants belonged to EnP, while the remaining two-thirds were corresponding with EnB, respectively. This is consistent with other studies that reported that gut microbiota of urban people occupied Bacteroides rather than Prevotella [ 32 , 75 , 76 ]. Other enterotypes could not be detected in our dataset.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, one-third of all participants belonged to EnP, while the remaining two-thirds were corresponding with EnB, respectively. This is consistent with other studies that reported that gut microbiota of urban people occupied Bacteroides rather than Prevotella [ 32 , 75 , 76 ]. Other enterotypes could not be detected in our dataset.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the results of previous studies [23,25,29,[32][33][34]44], this study found that Blautia, Faecalibacterium, Bifidobacterium, Clostridium, Anaerostipes, Mediterraneibacter, and Butyricicoccus abundances were relatively higher in healthy fecal samples than in prediabetic fecal samples. Anaerostipes and Faecalibacterium can help maintain the integrity of the intestinal mucosa by producing butyrate.…”
Section: Discussionsupporting
confidence: 91%
“…To address the relationships between consumed foods and gut microbiota more directly, we performed cross-sectional studies in two countries, Mongolia [ 55 ] and the Philippines [ 56 , 57 ]. In each country, we collected food consumption data as well as gut microbiome data in urban and rural sites.…”
Section: Gut Microbiota Of Asian People Associated With Lifestyle Dis...mentioning
confidence: 99%